Behaviour Management and Digital Technology: Strategies for Managing an Effective and Organized Classroom - Fatimah, Umi; Pitaloka, Ami Widya; Cahayati, Era; Bektiarso, Singgih (Universitas Cenderawasih, 2025)
The development of digital technology and student behaviour management requires educators to develop more effective and organized classroom management strategies. This article discusses the integration of behaviour management with digital technology in the context of modern classroom management. The research objective is to identify and analyze effective strategies for creating an organized learning environment by utilizing digital technology as a supporting tool for student behaviour management. The approach used is qualitative-descriptive through literature review analysis or literature study. The research results show that the combination of behaviour management with digital technology can increase the effectiveness of classroom management through a student behaviour monitoring system, the use of gamification in learning and personalization of learning. This research concludes that the use of digital technology in behaviour management has a positive impact on classroom organization, student engagement, and achievement of learning goals. The implications of this research provide practical guidance for educators in integrating digital technology to create a more effective and structured learning environment.